Examining the components of freedom values in contemporary Chinese society - Zhang, Yue; Huang, Heshui; Tian, Jiao (Frontiers in Psychology, 2024)
Introduction This research paper delves into the structure and connotation of freedom values within contemporary Chinese society, taking into account the historical, societal, and cultural context. Methods To achieve this, a multifaceted approach was adopted, integrating literature analysis, focus group interviews, in-depth interviews, and questionnaire surveys. Results The study culminated in the development of a comprehensive conceptual model comprising five distinct dimensions: behavior within boundaries, independence without interference, autonomy with responsibility, rights with guarantee, and equality without domination. Discussion This conceptual model successfully consolidates the prevailing consensus on freedom values among the Chinese populace, offering a robust framework for the propagation and nurturing of freedom within Chinese society. The insights gleaned from this research deepen our comprehension of freedom values and furnish valuable guidance for academics, policymakers, and practitioners keen on advancing freedom and societal well-being.